2011
DOI: 10.1007/s10620-011-1784-x
|View full text |Cite
|
Sign up to set email alerts
|

Lemon Verbena Infusion Consumption Attenuates Oxidative Stress in Dextran Sulfate Sodium-Induced Colitis in the Rat

Abstract: Our study shows that the preventive consumption of lemon verbena infusion offered some antioxidative protection during experimental colitis by stimulating SOD activity and decreasing lipid peroxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…However, a study using a cocoa diet in a dextran sodium sulfate (DSS) model demonstrated that cocoa intake did not improve clinical colitis, although it certainly contributed to reducing colonic oxidative activity and serum inflammatory mediator concentrations (Pérez-Berezo et al, 2012a). These results agree with those obtained with luteolin and with a lemon verbena infusion rich in polyphenolic compounds (Karrasch et al, 2007; Lenoir et al, 2011). More interestingly, it has recently been reported that a polyphenol-enriched cocoa extract was able to decrease acute DSS colitis in mice (Andújar et al, 2011), thus evidencing the need for a high polyphenol content in the cocoa to achieve anti-inflammatory activity in the IBD.…”
Section: Anti-inflammatory Potential Of Cocoasupporting
confidence: 91%
“…However, a study using a cocoa diet in a dextran sodium sulfate (DSS) model demonstrated that cocoa intake did not improve clinical colitis, although it certainly contributed to reducing colonic oxidative activity and serum inflammatory mediator concentrations (Pérez-Berezo et al, 2012a). These results agree with those obtained with luteolin and with a lemon verbena infusion rich in polyphenolic compounds (Karrasch et al, 2007; Lenoir et al, 2011). More interestingly, it has recently been reported that a polyphenol-enriched cocoa extract was able to decrease acute DSS colitis in mice (Andújar et al, 2011), thus evidencing the need for a high polyphenol content in the cocoa to achieve anti-inflammatory activity in the IBD.…”
Section: Anti-inflammatory Potential Of Cocoasupporting
confidence: 91%
“…56,57 Surprisingly, the amount of glutathione in its reduced (GSH) and oxidized (GSSG) forms in inflamed colon was not affected by colitis, despite presumed intense production of reactive oxygen and nitrogen oxidative species. 58 These results that were already observed in previous studies using the model of DSS-induced colitis, 49,50,59 suggest that the colonic content in glutathione can be dissociated from regulating major inflammation, at least in this experimental model.…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, most studies have focused on the effects of dietary supplementation before and/or during the induction of colitis. 39,[49][50][51][52] This is related to the fact that only recently has emerged MH as a therapeutic goal that would allow diminishing the risk of relapse in patients in remission for IBD. 8 , colitis was induced in rats by adding DSS in the drinking water for 6 days.…”
Section: Discussionmentioning
confidence: 99%
“…28 Previous research has only investigated the dynamic parameters of their free radical scavenging activities with respect to hydroxyl radical scavenging, so new data are needed for other radicals. VO is widely used for the treatment of anxiety and unrest.…”
Section: Discussionmentioning
confidence: 99%